The Role Of The Ranting Muhammadiyah Jemundo In The Community Through Education And Cultural Missionary Endeavor - Dwi Yulia Ningsih; Muhlasin Amrullah; Aisyah Cucu Utami; Rida Septi Rifana; Putri Kusumaningtyas; Sultan Muhammad (Proceedings of The ICECRS, 2020)
This research aims to know the act of Ranting Muhammadiyah Jemundo to improve people pass through education and cultural missionary endeavour for better ahead. The method of this research is a descriptive qualitative method, interview, and observation altogether. According to the research, Ranting Muhammadiyah Jemundo does within the superior program to improve the people through education and cultural missionary endeavour that carried out together in that organization. Muhammadiyah is one of the most bigger religion organization and owned a lot of congregants all around Indonesia. With based on Amar Ma’ruf Nahi Munkar, a congregant of Muhammadiyah can be said that quite successful in several sectors, for example, in the economy sector, education, and enlightenment sector. The purpose of this research is to know about history, society condition, tradition, culture, and the situation in Ranting Muhammadiyah Jemundo and also to know the programs, challenges, and the breakthroughs inside the Ranting Muhammadiyah Jemundo. This research use the interview method as the main method and continued by observation to endue and maximize the result of thiss research. The result that be found from this research include the history about establishment of Ranting Muhammadiyah Jemundo, the programs, society condition, the breakthroughs of Ranting Muhammadiyah Jemundo to confront any challenge, and also the way Ranting Muhammadiyah Jemundo did to enlight and to properous people’s life.